A New Method for Heavy Metals and Aluminium Detection using Biopolymer-based Optical Biosensor - Ling, Shing Wong; Chee, Sien Wong (IEEE, 2015)
A biopolymer-based biosensor for heavy metals and aluminium (Al) detection was constructed with naturally occurring β-carotene in palm kernel oil used as the biological reporter. The biosensor was designed with β-carotene entrapped by polyurethane- a polymer formed through prepolymerization of palm kernel oil. The presence of copper (Cu), lead (Pb), zinc (Zn), and Al was detected through the emulsification of β- carotene, which caused the change of optical density (OD) at λ = 450 nm. The results showed the OD increased with the presence of heavy metals and Al within 0.1 mg/L – 10.0 mg/L. The biosensor was constructed without extra steps to immobilize the biological component and it was simple to use with one step detection. Together with high reproducibility and fast response to Cu within 15 minutes, the biosensor showed good potential to be developed as a method to detect the presence of heavy metals and Al.